Comparison of various UHMWPE formulations from contemporary total knee replacements before and after accelerated aging - Petr Fulin; Veronika Gajdosova; Ivana Sloufova; Jiri Hodan; David Pokorny; Miroslav Slouf (Materials & Design)
We have collected 21 different formulations of ultrahigh molecular weight polyethylene (UHMWPE), which have been employed as liners in contemporary total knee replacements (TKR). The UHMWPE liners were bought from the most important manufacturers on the orthopedic market in the Czech Republic as of 2020. The collected liners represented a broad range of both traditional and modern UHMWPE formulations, which differed by the level of crosslinking, type of thermal treatment, sterilization and/or stabilization. All obtained UHMWPE’s were characterized by multiple methods immediately after purchase and after the accelerated aging in H2O2. The experimental results (oxidative degradation, structure changes, and micromechanical properties) were correlated with manufacturer’s data (crosslinking, thermal treatment, sterilization, and stabilization). The investigated UHMWPE liners exhibited significant differences in their properties, namely in their resistance to long term oxidative degradation. The stiffness-related mechanical properties showed a strong correlation with the overall crystallinity. The crystallinity depended mostly on the oxidative degradation of the UHMWPE liners, while the thermal treatment played a minor role. The highest resistance to oxidation and wear, which promises the best in vivo performance, was found for the crosslinked UHMWPE formulations with biocompatible stabilizers (such as α-tocopherol, which is the key component of vitamin E).